Seroprevalence and clinical manifestations of Chikungunya infection in Makassar city, Indonesia - Emelia Abdullah, Nurul Pausi; Hatta, Mochammad; Rosser, Joelle I; Sjahril, Rizalinda; Fadhilah; Murni; Nursehang; Wahid, Isra (Gaceta Médica de Caracas, 2024)
Background: Chikungunya is a vector-borne disease with a high morbidity rate, spread in dengue hemorrhagic fever endemic areas because the vector carrying the virus is transmitted by the same mosquitoes, namely Aedes Aegypti and Aedes Albopictus. The number of mosquito breeding sites is often associated with an increased incidence of chikungunya disease. The proximity of mosquito breeding sites to human habitation is a significant risk factor for chikungunya. Data related to chikungunya is still lacking in Makassar. This study aims to understand the prevalence of CHIKV infection through serodiagnosis by measuring CHIKV IgG antibodies and looking at the history of clinical symptoms associated with CHIKV infection in Makassar to reduce widespread transmission.